The impacts of intellectual capital, market size, and intellectual property factors in geothermal power exploration - Alsaleh, Mohd; Abdul-Rahim, A.S. (SAGE Publications, 2024)
There are many advantages of geothermal energy, as an environmentally friendly resource; however, for these benefits of geothermal power to be fully maximized, there are some problems that need to be addressed. The primary objective of this research was to examine the influence of intellectual property (IP) rights and economic growth on the geothermal energy output among the 27 European countries within the time frame 1990 to 2021. This study adopts auto-regressive distributed lag (ARDL). The findings show that a significant increase in the geothermal energy industry sustainability can occur in EU14 emerged economies using IP rights than in EU13 emerging economies. The major contributions of the research are that among additional factors, intellectual capital, market size, intuitional quality, and economic growth contribute more positively to geothermal energy sustainability in EU14 emerged economies than in EU13 emerging economies. Results from the analysis show geothermal power sustainability among the 27 European countries could be boosted significantly by adequately putting in place the determining factors of IP as this will foster the attainment of aims behind the energy union by the year 2030. This will no doubt be of help in curbing climate change and environmental pollution in society. The projected calculations were validated through the three estimators adopted for this study, that is, the pooled mean group, mean group, and dynamic fixed effect. The policy implication pointed out by this study the European nations in this study need to make IP indicators to be more effective as this helps in achieving societal and environmental goals. Moreover, the authorities in charge of lawmaking in European countries should focus more on IP areas to ensure the sustainability of geothermal energy generation. Also, authorities in charge of policymaking in the European nations should foster commixture strategies that are sustainable in enhancing IP breakdown as this will assist in fostering geothermal power exploration, thereby reducing the need for fossil fuels which will also carbon dioxide emission in the years to come. © The Author(s) 2023.